The stuff of thought : language as a window into human nature - Pinker, Steven, 1954- (Penguin Books, 2008)
Presents a study of the relationship between language and human nature, explaining how everything from swearing and innuendo to prepositions and baby names reveals facts about key human concepts, emotions, and relationships.